Hubungan Kuliah Penunjang dengan Pencapaian Learning Objectives Blok Hematologi Mahasiswa Pendidikan Dokter Fakultas Kedokteran Universitas Sebelas Maret Surakarta - Dwiyono, Rizqi Ahmad Nur; FK UNS, Murkati; Putranto, R. Prihandjojo Andri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: There are 5 types of lecture available in PBL learning method model in Faculty of Medicine Universitas Sebelas Maret, namely: (1) introductory lecture, (2) supporting lecture, (3) final lecture, (4) workshops, and (5) courses. Supporting lecture is defined as lectures of subjects which are required to be understood by students, but not yet covered in tutorials, practical laboratory works, skills lab, or field lab. The present study aims to determine the relationship between given supporting lecture and the attainment of learning objectives which are designed as the implementation as the competency standard which has to be achieved by medical students. Method: The present study was an experimental quotient study, conducted by pretest posttest with control group. Obtained samples were divided into 2 groups, namely: group A and group B. Pretest was conducted on both groups, before group A had not received the supporting lecture. While, posttest was conducted on both groups, when group A had receveived the supprting lecture. Collected data was analyzed by using McNemar test and processed with Statistical Package for Social Sciences 20 ( SPSS 20 ) for Windows Release and p < 0.05 indicated signification. Result: The highest learning objectives attainment increase was seen on group A by 52%, while on group B was 4%. McNemar test showed there is a statistically significant difference on group A with p = 0.000 (p < 0.05) and no significant difference on group B with p = 0.05. Conclusions: There is a significant relationship between given supporting lecture and the attainment one of Learning Objectives of Hematology which is only able to be fulfilled by supporting lecture in students of Faculty of Medicine Universitas Sebelas Maret Surakarta. Keywords: supporter lecture, learning objectives, problem based learningÂ